COMBINED GENETIC RISK SCORE FOR LIVER CIRRHOSIS PREDICTION IN CHRONIC HEPATITIS C: COMPARATIVE EVALUATION OF FIVE POLYMORPHISMS AND THEIR CUMULATIVE CONTRIBUTION (European Journal of Interdisciplinary Research and Development, 2026)
Background and Aim. Individual genetic polymorphisms demonstrate only moderate predictive accuracy for liver cirrhosis (LC) in chronic hepatitis C (CHC). Polygenic approaches that combine multiple loci covering distinct pathogenetic pathways may substantially improve risk prediction. This study aimed to develop a combined genetic risk score based on five polymorphisms (TNF-α G308A, IL28B C/T, VEGFA C936T, MMP9 Gln279Arg, SOD2 Ala16Val) and to evaluate its diagnostic performance in comparison with individual loci and standard clinical indices. Materials and Methods. 93 CHC patients were enrolled: Group I comprised 48 patients without cirrhosis (F0–F3 by METAVIR) and Group II comprised 45 patients with verified cirrhosis (F4). All five loci were genotyped by real-time PCR with TaqMan probes. A cumulative score (0–10) was calculated by assigning 0–2 points per locus (0 = protective homozygote, 1 = heterozygote, 2 = risk homozygote). ROC analysis with AUC calculation was performed. AUC comparisons were made using the DeLong method. Results. A score ≥6 was found in 64.4% of cirrhosis patients vs. 16.7% of non-cirrhotic patients (χ²=22.87; p1.0 yielded AUC=0.86 (95% CI 0.78–0.93), specificity 91.7%, and PPV 87.5%. The genetic score correlated with MELD (r=0.47; p